Epidemiology, Etiology, Clinical Description, and Prevention of Postoperative Cognitive Dysfunction (Eurasian Research Bulletin, 2023)
General anesthesia can cause damage to the central nervous system (CNS) that occurs in the postoperative period, among such injuries, postoperative cognitive impairment (POCD) takes the main place, and it can develop in patients of any age, without a history of psychoneurological diseases. Postoperative cognitive disorders worsen the quality of life of patients, make it difficult for them to perform their professional work and social tasks, which has become an urgent problem of modern anesthesiology in recent years1. When the prevalence of POCD was determined, it ranged from 7% for minor surgery at 1 week and 3 months postoperatively to 17% and 41% for major surgery at 3 months.